Apakah APAKAH PENGETAHUAN MEMENGARUHI KESIAPAN MENTAL IBU DALAM MENGHADAPI KEHAMILAN? - Andreinie, Ria; Zelharsandy, Vika Tri (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2025)
Teenagers are vulnerable to various risky behaviors, including early marriage which can have negative impacts on physical and psychosocial health. The phenomenon of early marriage still occurs at a fairly high rate, reported to be around 25% of total marriages in Indonesia involving individuals under the age of 16. One of the main impacts of early marriage is early pregnancy, which can bring great challenges for young mothers, both physically and mentally. This study aims to analyze the relationship between knowledge about early pregnancy and mental preparedness for pregnancy. The research method is quantitative with a descriptive correlational design. The research sample was prospective brides or primigravida pregnant women, aged less than 20 years who live in Tanjung Baru Village. The results showed that all respondents had knowledge of early pregnancy in the moderate category, all respondents were classified as not mentally ready to face pregnancy, and there was a significant relationship between knowledge about early pregnancy and mental readiness to face pregnancy (r = 0.430; p-value 0.020). This finding confirms the importance of adequate knowledge about early pregnancy in influencing the mother's mental readiness.